Environmentally clean micromilling of electron beam melted Ti6Al4V. (1st October 2016) - Bruschi, S.; Tristo, G.; Rysava, Z.; Bariani, P.F.; Umbrello, D.; De Chiffre, L.
Abstract: The paper is aimed at evaluating the performances of Minimum Quantity Lubrication (MQL), dry cutting and cryogenic cooling when applied to the micro-milling of Ti6Al4V titanium alloy samples obtained by Additive Manufacturing (AM) using the Electron Beam Melting (EBM) technology. The micro-milling tests were carried out on a high precision 5-axis micro-milling center, at varying cutting speed and feed per tooth. The performances of the different lubrication/cooling strategies were analyzed in terms of surface integrity, namely surface topography, nano-hardness and sub-surface microstructural alterations, in order to prove the impact of clean cutting conditions when applied to micro-machining of a AM titanium alloy of biomedical interest. It is shown that dry cutting assures the same performances of MQL, representing then the most suitable option to decrease the environmental impact of the machining process. Highlights: Micro-milling of EBM Ti6Al4V was carried out under MQL, dry and cryogenic condition. Different cutting speeds and feed rates were utilized. Surface quality and burrs formations are mainly influenced by the feed per tooth. The lubrication condition weakly influences the cutting performances.